Long exposure of argon plasma coagulation induces more thermal damage accompanied by a higher expression of NF-?B and caspase-3 - Rahmat Wariz; Keng-Liang Ou; Muhammad Ruslin; Bahruddin Thalib; Chung-Ming Liu; Hsin-Hua Chou (Journal of Dentomaxillofacial Science, 2018)
Objective: Long exposure of argon plasma coagulation (APC) causes thermal damage and apoptosis in tissues. However, whether the APC-induced thermal damage in tissues involves the expression of NF-ÎºB and caspase-3 remains undetermined. In this study, we compared the effect of APC on liver damage at two different exposure time and tested the hypothesis that thermal injuries induced by APC are accompanied by induction of NF-ÎºB and caspase-3 expression in rat liver.Material and Methods: Liver injuries were induced in rats by an APC device with pulse mode for 2 or 4 seconds under the same frequency of power (40W). The animals were sacrificed 0, 3, 7 and 21 days after injury and the liver tissues were harvested and used for western blotting, histological and immunohistochemical analyses.Results: Haematoxylin and eosin (H&E) stained sections of the liver tissues showed that two-second application of APC caused minimum thermal damage and apoptotic areas, less carbonization, and more fibrosis formation in liver than the four-second APC application at all time points examined. All of these APC-induced thermal effects and morphological changes in the two-second APC application group but not the four-second APC application group recovered 21 days after the treatment. Western blot results indicated that APC induced the expression of NF-ÎºB on day 3, and peaked on days and 14. In the two-second APC application group, the expression of NF-ÎºB returned to the normal level on day 28. However, the expression of NF-ÎºB induced by 4 seconds of APC application remained high even 28 days after injury. The expression of caspase-3 induced by the 2 seconds or 4 seconds of APC application peaked at 7 or 14 days, respectively. Similarly, the APC-induce expression of caspase-3 returned to the normal level in the 2-second APC application group, but it still remained high in the 4-second APC application group even 28 days after injury. These results were further confirmed by The immunofluorescence data also indicated that APC exposure for 4 seconds induced a much higher expression of NF-ÎºB than APC exposure for 2 seconds. The similar pattern was observed in the caspase-3 expression.Conclusions: Taken together, our results show that 2-second APC exposure causes minimum liver injury accompanied by the expressions of NF-ÎºB and casapase-3 which return to the normal level 28 days after injury. These findings strongly suggest that the shortest pulse mode (2 seconds) application of APC is a safe, convenient, and effective approach for the treatment of particularly thermosensitive tissues.